José Rizal’s Noli me tángere and theMaking of a Cultural Artifact - Garinto, Leif Andrew B. (Archīum Ateneo, 2024)
José Rizal’s Noli me tángere (Touch Me Not) is pivotal in shaping Philippine national identity and literary tradition. While the novel has remained in continuous print, it has evolved from a material text into a revered cultural artifact. This article critically investigates the processes through which the Noli has been institutionalized as a foundational text, focusing on the intersections of colonialism, publishing, and education that have sustained its prominence. The American colonial administration’s strategic appropriation, along with its publication history and integration into the educational curriculum, transformed this once subversive work into a canonical symbol of Filipino nationhood.